Invested interests : capital, culture, and the World Bank - Benjamin, Bret (University of Minnesota Press, 2007)
In Invested Interests, Bret Benjamin contends that the World Bank has, from its inception, trafficked in culture. From the political context in which the Bank was chartered to its evolution into an interventionist development agency with vast, unchecked powers, Benjamin explores the Banks central role in the global dissemination of Fordist-Keynesianism, its conflicted support for nationalism and the nation-state, and its emerging awareness of the relationships between economics and culture.